Variability of standard artificial soils: Physico-chemical properties and phenanthrene desorption measured by means of supercritical fluid extraction - Bielská, Lucie; Hovorková, Ivana; Komprdová, Klára; Hofman, Jakub (Environmental pollution (Barking, Essex, 2012)
The study is focused on artificial soil which is supposed to be a standardized "soil like" medium. We compared physico-chemical properties and extractability of Phenanthrene from 25 artificial soils prepared according to OECD standardized procedures at different laboratories. A substantial range of soil properties was found, also for parameters which should be standardized because they have an important influence on the bioavailability of pollutants (e.g. total organic carbon ranged from 1.4 to 6.1%). The extractability of Phe was measured by supercritical fluid extraction (SFE) at harsh and mild conditions. Highly variable Phe extractability from different soils (3-89%) was observed. The extractability was strongly related (R(2)=0.87) to total organic carbon content, 0.1-2mm particle size, and humic/fulvic acid ratio in the following multiple regression model: SFE (%)=1.35*sand (%)-0.77*TOC (%)2+0.27*HA/FA.
Keywords: Adsorption; Chromatography, Supercritical Fluid; Phenanthrenes; superkritická fluidní chromatografie; látky znečišťující půdu; Soil Pollutants; Soil; půda; fenantreny; adsorpce